Heat Stress Indicators in CMIP6: Estimating Future Trends and Exceedances of Impact‐Relevant Thresholds. Issue 3 (10th March 2021) - Schwingshackl, Clemens; Sillmann, Jana; Vicedo‐Cabrera, Ana Maria; Sandstad, Marit; Aunan, Kristin
Abstract: Global warming is leading to increased heat stress in many regions around the world. An extensive number of heat stress indicators (HSIs) has been developed to measure the associated impacts on human health. Here we calculate eight HSIs for global climate models participating in the Coupled Model Intercomparison Project Phase 6 (CMIP6). We compare their future trends as function of global mean temperature, with particular focus on highly populated regions. All analyzed HSIs increase significantly ( p  < 0.01) in all considered regions. Moreover, the different HSIs reveal a substantial spread ranging from trends close to the rate of global mean temperature up to an amplification of more than a factor of two. Trends change considerably when normalizing the HSIs by accounting for the different scales on which they are defined, but the large spread and strong trends remain. Consistently, exceedances of impact‐relevant thresholds are strongly increasing globally, including in several densely populated regions, but also show substantial spread across the selected HSIs. The indicators with the highest exceedance rates vary for different threshold levels, suggesting that the large indicator spread is associated both to differences in trend magnitude and the definition of threshold levels. These results highlight the importance of choosing indicators and thresholds that are appropriate for the respective impact under consideration. Additionally, further validation of HSIs regarding their capability to quantify heat impacts on human health on regional‐to‐global scales would be of great value for assessing global impacts of future heat stress more reliably. Plain Language Summary: Heat stress caused by high levels of air temperature and humidity is rising globally due to climate change. Various indicators for heat stress have been developed to quantify different facets of how heat impacts people. We use data from climate models to calculate the future evolution of eight heat stress indicators for highly populated regions of the world. The trends of the different indicators vary substantially, with some indicators showing large increases while others only increase modestly. For estimating the severity of heat stress, we calculate how often each indicator exceeds threshold values that indicate different heat stress severity. Many thresholds will be exceeded much more often with rising temperatures. The increases are particularly large for some indicators while others only show small increases. Moreover, the indicators with the strongest trends are often not the ones that show the highest increase in threshold exceedances. For quantifying the impacts of heat stress caused by climate change it is thus important to choose indicators that are appropriate for the respective application. While several indicators were tested on small scales (e.g., in cities or single countries), for global heat stress assessments it is necessary to have more validation studies on regional‐to‐global scales. Key Points: All heat stress indicators increase statistically significantly with global mean temperature but trends reveal a substantial spread Exceedances of impact‐relevant thresholds are strongly increasing globally including in several densely populated regions For assessing heat‐related health impacts only indicators and thresholds should be chosen that were validated for the respective application